PEMBELAJARAN BAHASA INDONESIA BERBASIS STRATEGI BELAJAR BAHASA SEBAGAI PENDUKUNG IMPLEMENTASI KURIKULUM 2013 - Lisnawati, Iis (Jurnal Pendidikan Bahasa dan Sastra, 2014)
The scientific approach (observing, questioning, associating, experimenting and networking) employed in the 2013 curriculum requires students to not only master, experiment and create concepts but also to communicate results of analysis, findings or products to other students/parties. Indonesian teaching, therefore, is oriented not only for mastery of grammatical competence but also sociolinguistic, discourse ad strategic competences. To acquire such competences, an appropriate teaching strategy is called for. One such strategy is the so-called the language learning strategy, which refers to specific actions carried out by students to make learning easier, faster, more enjoyable, more independent, more effective and more directed towards new situations. This strategy includes memory, cognitive, compensation, metacognitive, affective and social strategies.